The natural geographical factors motivating Turkey's pivotal role - , reser. Ghassan kadhum hanoon; Dr.Esraa Kazem Al -Husseini (Journal of College of Education, 2024)
The research aims to study the impact of the natural factors motivating Turkey’s pivotal role in West Asia, especially after the Justice and Development Party’s control of the government and the expulsion of the opponents of the advocates of Ataturkism, which was the cause of the deterioration of the economic and political conditions of Turkey, as Turkey was able to turn into an economic and political state par excellence. Its strategic geographical location in the region, which is located at the crossroads of the three continents of the world, in addition to its possession of large sea coasts overlooking the warm seas, made it a transit area for energy resources for European countries and the world, while Turkey possessed large land borders whose land borders were estimated with neighboring countries (26,480) km Despite the large area of ​​the Turkish state, it was able to control all its lands in a manner that serves the power of the state due to its ethnographic composition, especially religious, and Turkey also possesses huge natural resources of natural resources, especially water resources, which exceed their counterparts from neighboring countries.
Keywords: geographical location, strategic location, borders, area, water resources